Using a Steroid-sparing Tool in Paediatric Inflammatory Bowel Disease to Evaluate Steroid Use and Dependency. Issue 5 (November 2019) - Harris, Rachel E.; Sim, Wei; Sutton, Harry; Garrick, Vikki; Curtis, Lee; Gervais, Lisa; Merrick, Victoria; Barclay, Andrew R.; Flynn, Diana M.; Tayler, Rachel; Hansen, Richard; Russell, Richard K.
ABSTRACT: Objectives: The aim of the study was to evaluate the use of steroids within the paediatric inflammatory bowel disease (PIBD) population at a tertiary paediatric centre over a year; to identify cases of steroid dependency; and assess factors associated with steroid excess. Methods: The prevalent PIBD population (May 1, 2017–April 30, 2018) were reviewed. Data were collected retrospectively from patient records and entered into an online steroid assessment tool (modified for paediatrics). Results: A total of 229 patients (181 Crohn disease, 31 ulcerative colitis [UC], and 17 inflammatory bowel disease–unclassified) were included. Of the 229 patients 38 (16.6%) received oral steroids; 12 of 38 (31.6%) receiving >3-month course. Eleven of 38 (28.9%) received >1 steroid course (maximum 2). Of the 229 patients 37 (16.2%) had exclusive enteral nutrition, with 26 of 37 (11.4% total cohort) avoiding steroid use during the study period. Quiescent disease activity had a negative correlation with steroid use (11/127 [8.7%] vs 27/102 [26.5%] P  < 0.01), and steroid dependency (3/127 [2.4%] vs 12/102 [11.8%] P  < 0.01). Patients with UC were more likely to be steroid dependent (5/31 [16.1%] UC vs 10/198 [5.1%]; P  = 0.02); as were network-managed patients (8/11 [72.7%] vs 7/27 [25.9%]; P  = 0.01). Fourteen of 15 (93.3%) of steroid-dependent patients had active steroid sparing strategies in place (eg, commencement, switching, or optimization of therapies). Conclusions: We have described rates of steroid use and dependency within our PIBD population. Exclusive enteral nutrition served as a steroid sparing tool in 11.4% of the total cohort. Replication of this study in other paediatric centres would allow comparative analysis.